A verdade como correção e Alétheia uma reconstrução do problema da verdade em Heidegger. - Gomes, Charlington Alves (2009)
The present dissertation intends to favor a significant contribution to the clear comprehension of the matter of truth from Heidegger, in such a way it surpasses the problematic raised by his thought, having, however, as principle focus, a reconstruction or re-reading of Heidegger investigations before the tradition, History of Philosophy, and show the metaphysical insufficiency concerning the comprehension of the truth of the being. We started from an investigation of ancient Ontology, which has as principal figure, Platoon, which according to Heidegger, is responsible for the original curve of truth: platonic conception of truth as correction, ratified by Aristóteles with the agreement concept; perpetuated concepts throughout the History of Philosophy as Metaphysics. Nevertheless, Heidegger does not treat metaphysics in a negative way, but as a place where all the problems, while question for Philosophy, get together, that is why in Heidegger existing analytics, it is necessary to step back towards appropriate comprehension, with no curves, no forgetting, that is, in such a way the thought surpasses and corrects the lack caused by metaphysics, that is why it is necessary to recover the truth as Alethéia = uncovering. In accordance with truth as correction, Heidegger ontology for truth lies in the existing ontological possibility of Dasein. Heidegger wants the truth of origin: Let-it-be, uncovering, non-concealing, Alethéia. Of origin because the word Alethéia lies in the origin of the Greek thought, of philosophy, of Heraclitus . The dissertation still brings the problem of truth in modern science and language. All the questions raised in the dissertation are upon the chive of Heidegger thought, that is why in the second part of the dissertation we treat the question of truth leaning on the existing phenomenon condition of the analytics of Heidegger: In a construction of a new ontology, this being of ontological hermeneutic nature, of the world, of men, of the truth.